Impact of an Ambulatory Clinical Pharmacy Population Health Initiative on HbA1c Reduction and Value-Based Measures: A Retrospective, Single-Center Cohort Study - Savannah Nelson; Tasha A. Butler; Amanda Martinez; Jessica Bianco; Delilah Blanco; Nicholas W. Carris (Diabetology)
Background: Studies of pharmacists’ clinical programs have demonstrated improvements in controlling chronic diseases. However, significantly less data are available regarding pharmacist impact in a value-based Patient-Centered Medical Home (PCMH). The present study assessed a population health initiative to incorporate pharmacists for the management of type 2 diabetes (T2D), hypertension, and hyperlipidemia in a PCMH. Methods: This was a single-center retrospective cohort study of patients with T2D and baseline glycated hemoglobin (HbA1c) greater than 9%. Patients were excluded if they received care from an endocrinology provider or were lost to follow-up during the observation window of 1 January 2023 through 31 July 2023. Patients were analyzed in two cohorts: (1) patients who received any outpatient care from a clinical pharmacist (pharmacist cohort) and (2) patients who did not receive any outpatient care from a clinical pharmacist (usual care cohort). The primary outcome was the proportion of patients achieving an HbA1c of less than 8%. Secondary outcomes included blood pressure control and receipt of guideline-directed statin therapy. Results: Ninety-one patients were identified, twenty-nine in the pharmacist cohort and sixty-two in the usual care cohort. The overall population was older (mean age ~66 years), 59% female, and racially diverse (<50% Caucasian). HbA1c less than 8% was achieved in 34% of patients in the pharmacist cohort and 29% of patients in the usual care cohort (p = 0.001). A blood pressure goal of less than 140/90 mmHg was achieved more frequently in the pharmacist cohort (90% vs. 61%, p = 0.006), but guideline-directed statin therapy was similar between groups (90% vs. 79%, p = 0.215). Conclusions: Pharmacists can play an integral role within a PCMH to improve value-based measures for HbA1c and blood pressure control. Further research is needed to assess the impact of pharmacist care on statin use and economic outcomes.